Gut microbiome interacts with pregnancy hormone metabolites in gestational diabetes mellitus - Lyu, Xuejing; Wang, Shaona; Zhong, Jiaxin; Cai, Lingzhu; Zheng, Yanhui; Zhou, Ying; Zhou, Ying; Chen, Qionghua; Li, Qiyuan (Frontiers in Microbiology, 2023)
Introduction Change in the composition of intestinal microbiota is associated with metabolic disorders such as gestational diabetes mellitus (GDM). Methods To understand how the microbiota impacts the development of gestational diabetes mellitus, we profiled the intestinal microbiome of 54 pregnant women, including 27 GDM subjects, by employing 16S rRNA gene sequencing. Additionally, we conducted targeted metabolomics assays to validate the identified pathways with overrepresented metabolites. Results We evaluated the patterns of changing abundances of operational taxonomic units (OTU) between GDM and the healthy counterparts over three timepoints. Based on the significant OTUs, we inferred 132 significantly altered metabolic pathways in GDM. And identified two overrepresented metabolites of pregnancy hormone, butyrate and mevalonate, as potential intermediary metabolites of intestinal microbiota in GDM. Finally, we validated the impacts of the intestinal microbiota on GDM by demonstrating consistent changes of the serum levels of progesterone, estradiol, butyrate, and mevalonate in an independent cohort. Discussion Our findings confirm that alterations in the microbiota play a role in the development of GDM by impacting the metabolism of pregnancy hormones. This provides a novel perspective on the pathogenesis of GDM and introduces potential biomarkers that can be used for early diagnosis and prevention of the disease.